THE IMPACT OF E-PERFORMANCE ASSESSMENT AND CAREER PATH ON PERFORMANCE THROUGH WORK DISCIPLINE AS AN INTERVENING VARIABLE IN REGIONAL ORGANIZATION EMPLOYEES IN THE CITY OF SERANG - Wahyuni, Asti Dian Sri; Mukhlis, Ahmad; Permana, Angrian (Yayasan Education and Social Center, 2025)
Strategically, regional apparatus organizations (OPD) have an important role in the continuity of government, the division of tasks and authority is an effective way to achieve the stated goals. Achieving strategic targets cannot be separated from the employee's performance, so the importance of employee performance in achieving the goals that have been set as a whole by the agency This research was conducted on employees of regional organizations in Serang City with the aim of knowing and analyzing the effect of performance appraisal on employee performance, career path on employee performance, work discipline on employee performance, E-performance assessment on work discipline, career path on discipline work, E-performance assessment of employee performance through work discipline and levels of employee performance through work discipline. This research uses a quantitative method with a correlational design with a total population of 3,646 OPD employees in Serang City with sample determination using multiplication of the number of indicators with the highest value on the Likert scale so that the total sample used is 215 employees. The analysis method in this research uses regression analysis with the Smart PLS statistical tool. The results of the H1 test obtained a P-value of 0.199 > 0.05 and a T-Statistics value of 1.283 < 1.96 so that Ho was accepted and Ha was rejected, the results of the H2 test obtained a P-value of 0.000 < 0.05 and the T-value The statistics are 4.851 > 1.96 so that H0 is rejected and Ha is accepted, the results of the H3 test show a P-value of 0.000 < 0.05 and a T-Statistic value of 6.996 > 1.96 so that H0 is rejected and Ha is accepted, the results of the H4 test are obtained The P-value is 0.000 < 0.05 and the T-Statistic value is 7.354 > 1.96 so that H0 is rejected and Ha is accepted, the results of the H5 test show a P-value of 0.001 < 0.05 and a T-Statistic value of 3.182 > 1.96 so H0 is rejected and Ha is accepted, the results of testing H6 get a P-Values ​​value of 0.000 < 0.05 and T-Statistics of 3.555 > 1.98 so H0 is rejected and Ha is accepted, the results of testing H7 get a P-Values ​​value of 0.000 < 0.05 and T-Statistics of 4.136 > 1.98 so that H0 is rejected and Ha is accepted. Work discipline influences employee performance, career level influences performance and work discipline, and E-performance assessment and career level influence employee performance through work discipline. The study's findings indicate that while E-performance assessment has no effect on employee performance, it has a significant impact on work discipline.